105 Clinical and echocardiographic determinants of n-terminal pro b-type natriuretic peptide level in patients with stable chronic obstructive airways disease: a prospective observational study of 140 patients. (9th June 2011) - Gale, C P; White, J; Hunter, A; Owen, J; Watson, J; Pearson, I R; Holbrook, I; Durham, N; Pye, M
Abstract : Background: Brain natriuretic peptides have been shown to be reliable indicators of left ventricular failure and markers of risk in cardiac disease. However, patients with chronic obstructive pulmonary disease (COPD) are also known to have elevated concentrations of brain natriuretic peptides in the absence of overt cardiac disease, likely due to right ventricular strain. This has been shown to have prognostic value and has a potential role in the management of the condition; for example, it has been suggested that it could be used to guide the initiation of non-invasive ventilation. The aim of this study was to identify clinical and echocardiographic determinants of the polypeptide N-terminal pro-Brain Natriuretic Peptide (NT pro-BNP) in patients with stable COPD. Method: Arterial blood gases, plasma NT pro-BNP and transthoracic echocardiographic parameters were studied in 140 patients with stable COPD attending a respiratory outpatient clinic. Results: Of the 140 patients, 65 (46%) were male, 26 (19%) received home oxygen therapy, 115 (82%) were current smokers, 38 (27%) were prescribed diuretics and 15 (11%) had a left ventricular ejection fraction <45%. Patients with cor pulmonale (n=6) were more likely to have left ventricular systolic dysfunction (p<0.001), reduced tricuspid annular plane systolic excursion (p=0.017) and higher pulmonary artery systolic pressures (p=0.01). The median (IQR) NT pro-BNP concentration was 16.2 (25.4) pmol/l. Concentrations were significantly higher in those with a dilated left atrium, aortic stenosis, left ventricular systolic dysfunction, right ventricular impairment, atrial fibrillation and those prescribed diuretics and ACE inhibitors. Significant predictors of NT pro-BNP were a dilated left atrium, aortic stenosis and left ventricular systolic dysfunction. NT Pro-BNP was an excellent discriminator of RV impairment (C statistic=0.90). Conclusions: NT pro-BNP readily identifies patients with stable COPD who have right ventricular dysfunction. However, several other clinical variables also associated with increased NT pro-BNP concentrations are prevalent in this population. This is likely to confound clinical decision making.